2022
DOI: 10.11650/tjm/210803
|View full text |Cite
|
Sign up to set email alerts
|

Modulus-based Successive Overrelaxation Iteration Method for Pricing American Options with the Two-asset Black–Scholes and Heston's Models Based on Finite Volume Discretization

Abstract: In this paper we introduce a new numerical method for the linear complementarity problems (LCPs) arising from two-asset Black-Scholes and Heston's stochastic volatility American options pricing. Based on barycenter dual mesh, a class of finite volume method (FVM) is proposed for the spatial discretization, coupled with the backward Euler and Crank-Nicolson schemes are employed for time stepping of the partial differential equations (PDEs). Then, for the resulting time-dependent LCPs are solved by using an effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…Table 7 gives the RMS with different time steps for r = 0.1. Table 8 shows the relative errors and CPU times for the LBM, projected successive overrelaxation (PSOR) method, and modulus-based successive overrelaxation (MSOR) method [45] at r = 0.1. By comparing the above results it is shown that our proposed method has higher accuracy and takes much less CPU times.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Table 7 gives the RMS with different time steps for r = 0.1. Table 8 shows the relative errors and CPU times for the LBM, projected successive overrelaxation (PSOR) method, and modulus-based successive overrelaxation (MSOR) method [45] at r = 0.1. By comparing the above results it is shown that our proposed method has higher accuracy and takes much less CPU times.…”
Section: Numerical Simulationsmentioning
confidence: 99%